Die räumliche Ordnung in den Geschäftsvierteln von Karachi und Quetta (Pakistan). Ein Beitrag zur Diskussion über die jungen Wandlungen in der orientalischen Stadt - Scholz, Fred (ERDKUNDE, 1972)
Using the examples of Karachi and Quetta the article contributes to the discussion of the pattern of shopping centres in oriental cities and their recent changes. In both cities, first founded in the 19th century, state and private initiative worked side by side from the beginning in building up commercial life. While on the state side, enclosed markets and a closely bounded shopping quarter were laid out, private initiative led to a wild growth, a multiplicity of differentiation in the goods offered and to a spatial selection of commodity groups. In both cities there is within the shopping quarter and markets a centre-to periphery decline in the quality and quantity of the goods offered and a similarly directed change from concentration through association to mixing of commodity groups. In both cities the modern peripheral shopping streets form exceptions. The recent changes in the shopping quarters of Karachi and Quetta can, according to the investigations presented here, be regarded as the result of rational economic motivations and should not be treated either as the expression of oriental individuality or as westernisation.